UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENYIKAPI DAMPAK NEGATIF PENGGUNAAN INTERNET - Narsi Rajai; Saddam Husein (IAIN Ambon, 2021)
Abstract; This research aims to find out the negative impact of internet use on class VII students at Muhammadiyah Amaholu MTs and the efforts of Islamic Religious Education teachers in addressing the negative impact of internet use on class VII students at Muhammadiyah Amaholu MTs. The results showed that the negative impact of internet use on class VII students in MTs Muhammadiyah Amaholu District Huamual West Seram Regency among others: a) Students addicted to playing online games, b) Students do not concentrate on the subject matter in class, c) lazy to learn, d) lazy to do prayers five times, e) lazy to go preaching, and f) lazy to help parents at home. The efforts of Islamic Religious Education teachers in addressing the negative impact of internet use on class VII students in Muhammadiyah Amaholu MTs Huamual District of Western Seram Regency include: 1) Routinely give directions on internet use; 2) Taking/confiscating the student's mobile phone; 3) Give a reprimand or warning to students caught playing HP in class. We as pai teacher board together with the principal always give advice that students often learn to pay attention to their learning hours and appreciate the teacher council, respect both parents at home and appreciate the older in the community environment and then do not forget to read the Quran as a form of muslim person who obeys Allah Swt.Keywords: PAI Teacher Efforts, Negative Impact, Internet Abstrak; Penelitian ini bertujuan untuk mengetahui dampak negatif penggunaan internet pada siswa kelas VII di MTs Muhammadiyah Amaholu dan upaya guru Pendidikan Agama Islam dalam menyikapi dampak negatif penggunaan internet pada siswa kelas VII di MTs Muhammadiyah Amaholu. Hasil penelitian menunjukkan bahwa dampak negatif penggunaan internet pada siswa kelas VII di MTs Muhammadiyah Amaholu Kecamatan Huamual Kabupaten Seram Bagian Barat antara lain: a) Siswa ketagihan bermain game online, b) Siswa tidak konsentrasi terhadap materi pelajaran di kelas, c) malas belajar, d) malas mengerjakan sholat lima waktu, e) malas pergi mengaji, dan f) malas membantu orang tua di rumah. Upaya guru Pendidikan Agama Islam dalam menyikapi dampak negatif penggunaan internet pada siswa kelas VII di MTs Muhammadiyah Amaholu Kecamatan Huamual Kabupaten Seram Bagian Barat antara lain: 1) Rutin memberikan arahan tentang penggunaan internet; 2) Mengambil/menyita HP milik siswa; 3) Memberikan teguran atau peringatan kepada siswa yang kedapatan bermain HP di kelas. Kami selaku dewan guru PAI bersama kepala sekolah selalu memebrikan nasehat agar siswa sering belajar memperhatikan jam belajarnya serta menghargai dewan guru, menghargai kedua orang tua dirumah dan menghargai yang lebih tua dilingkungan masyarakat kemudian tidak lupa membaca AL Quran sebagai wujud pribadi muslim yang taat kepada Allah Swt.Kata kunci: Upaya Guru PAI, Dampak Negatif, Internet.